2018
DOI: 10.3389/fmicb.2018.02293
|View full text |Cite
|
Sign up to set email alerts
|

WadD, a New Brucella Lipopolysaccharide Core Glycosyltransferase Identified by Genomic Search and Phenotypic Characterization

Abstract: Brucellosis, an infectious disease caused by Brucella, is one of the most extended bacterial zoonosis in the world and an important cause of economic losses and human suffering. The lipopolysaccharide (LPS) of Brucella plays a major role in virulence as it impairs normal recognition by the innate immune system and delays the immune response. The LPS core is a branched structure involved in resistance to complement and polycationic peptides, and mutants in glycosyltransferases required for the synthesis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 52 publications
(107 reference statements)
2
18
0
Order By: Relevance
“…Similarly, there was no observable difference in survival ratio of the two strains when challenged with acidic environment (Figure 5A). Previously, the rough type Brucella strains have been described as being more sensitive to the bactericidal action of normal serum than their smooth counterparts (11). However, after incubation for 90 min in non-immune serum, we observed that the survival rate of RM57 was not significantly reduced compared to the parent strain M1981 (Figure 5A).…”
Section: Rm57 Shows No Sensitivity To Stress Conditionsmentioning
confidence: 54%
See 1 more Smart Citation
“…Similarly, there was no observable difference in survival ratio of the two strains when challenged with acidic environment (Figure 5A). Previously, the rough type Brucella strains have been described as being more sensitive to the bactericidal action of normal serum than their smooth counterparts (11). However, after incubation for 90 min in non-immune serum, we observed that the survival rate of RM57 was not significantly reduced compared to the parent strain M1981 (Figure 5A).…”
Section: Rm57 Shows No Sensitivity To Stress Conditionsmentioning
confidence: 54%
“…We evaluated the effect of bactericidal action in non-immune serum on sensitivity in Brucella strains according to a previously reported protocol (11). Briefly, cultures of RM57 and M1981 strains were adjusted to 10 4 CFUs/ml using PBS then dispensed in microtiter plates (at a volume of 30 µl/well) containing 60 µl of new-born bovine serum.…”
Section: Sensitivity Of Brucella Strains To the Bactericidal Action Omentioning
confidence: 99%
“…We discovered 14 such synthetic lethal genes in B. abortus (Fig. B and C) that have been previously reported to play a role in O‐polysaccharide synthesis (Cloeckaert et al ., ; Ugalde et al ., ; Guzman‐Verri et al ., ; Monreal et al ., ; Manterola et al ., ; Cardoso et al ., ; Lamontagne et al ., ; Gonzalez et al ., ; Mancilla et al ., ; Zhang et al ., ; Tian et al ., ; Dabral et al ., ; Salvador‐Bescos et al ., ); mutations in this gene set result in a rough phenotype in Brucella melitensis (Gonzalez et al ., ). It is well established that B. ovis is a stably rough strain that lacks LPS O‐polysaccharide (Gonzalez et al ., ; Tsolis et al ., ; Soler‐Llorens et al ., ; Mancilla, ).…”
Section: Resultsmentioning
confidence: 98%
“…The molecular connection between O-polysaccharide biosynthesis and the B. ovis chaining phenotype upon eipA depletion remains undefined, though it is known that alteration of LPS structure can influence morphology and division in C. crescentus (Cabeen et al, 2010). It has also been reported that teichoic acids, carbohydrate components of Gram-positive envelopes, play a role in the initiation of cell division (Santa Maria et al, 2014). EipA may serve in part as a bridge that links the state of envelope carbohydrates with the cell division apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we sought to identify genes that are dispensable in wild-type cells, but essential in the absence of eipA. We discovered 14 such synthetic lethal genes in B. abortus ( Figure 6B and C) that have been previously reported to play a role in O-polysaccharide synthesis (Gonzalez et al, 2008, Cardoso et al, 2006, Ugalde et al, 2000, Zhang et al, 2013, Tian et al, 2014, Mancilla et al, 2012, Cloeckaert et al, 2000, Dabral et al, 2015, Monreal et al, 2003, Guzman-Verri et al, 2002, Lamontagne et al, 2007, Manterola et al, 2005, Salvador-Bescos et al, 2018; mutations in this gene set result in a rough phenotype in Brucella melitensis (Gonzalez et al, 2008). It is well established that B. ovis is a stably rough strain that lacks LPS Opolysaccharide (Mancilla, 2015, Soler-Llorens et al, 2014, Tsolis et al, 2009, Gonzalez et al, 2008.…”
Section: Eipa Deletion Results In Sensitivity To Cell Envelope Stressorsmentioning
confidence: 99%